WACANA VERBAL DALAM KARIKATUR SURAT KABAR AL-JUMHÅªRIYYAH AL-YAMANIYYAH EDISI JULI-DESEMBER 2012: KAJIAN PRAGMATIK - , SIGIT RISTYA NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This analysis has an objective to find forms of speech act applied in conversation in caricature of the newspaper al-JumhÅ«riyyah al-Yamaniyyah edition of July-December 2012. Therefore, this study uses pragmatic analysis with contextual method in data analyzing. As a result, speech act by the function in conversation in caricature al-JumhÅ«riyyah al-Yamaniyyah Newspaper edition of July-December 2012 consist of locutionary, illocutionary, and perlocutionary act.